2015
DOI: 10.3233/cbm-150512
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of the association between DNMT3B-579G>T polymorphism and cancer risk

Abstract: DNMT3B-579G>T polymorphism might contribute to the susceptibility of cancers especially in the Asian population and for colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…For rs1569686, we consider it as a protective factor for gastric carcinogenesis and similar results were discovered in head and neck cancer, lung cancer and colorectal cancer (Duan et al, 2015, Zhang et al, 2015, Xia et al, 2015, Zhu et al, 2012). However, another study argued it was associated with poor prognosis in GC cases (Wang et al, 2015a).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…For rs1569686, we consider it as a protective factor for gastric carcinogenesis and similar results were discovered in head and neck cancer, lung cancer and colorectal cancer (Duan et al, 2015, Zhang et al, 2015, Xia et al, 2015, Zhu et al, 2012). However, another study argued it was associated with poor prognosis in GC cases (Wang et al, 2015a).…”
Section: Discussionsupporting
confidence: 54%
“…Previous meta-analysis studies primarily evaluated associations between a few SNPs and cancers without classification, such as GC (Zhu et al, 2015, Duan et al, 2015, Liu et al, 2015, Zhang et al, 2015, Xia et al, 2015). The major strengths of our study was its comprehensive and systematic focus on GC and SNPs from three main types of DNMTs , 17 SNPs in total.…”
Section: Discussionmentioning
confidence: 99%
“…For example, polymorphisms determining upregulation of gene transcription have been associated with an increased risk of developing lung cancer and head and neck carcinoma ( Shen et al, 2002 ; Liu et al, 2008 ). Based on meta-analysis data, a polymorphism in a DNMT3B regulative region has also been associated with reduced risk of cancer ( Zhu et al, 2012 ) but this point is still debated ( Xia et al, 2015 ).…”
Section: Alteration Of Dnmt3b Function In Human Diseasementioning
confidence: 99%
“…Moreover, we determined that the heterozygote GT genotype and the dominant model (GG vs. GT+TT) were associated with a reduced risk of colorectal cancer. Similarly, in a meta-analysis of 18 studies, Xia et al, (2015) reported that the heterozygous GT genotype and the dominant model (GT+TT) were associated with a reduced risk of the disease among the Asian population. A similar conclusion was presented by Zhu et al, (2012) who analyzed 11 studies (including 3513 cases and 3714 controls) to find different results in Asian and European populations.…”
Section: Discussionmentioning
confidence: 92%